Comprehensive Analysis of Neocaryamacrophylla Seed Oil: Physicochemical, Phytochemical, and Fatty Acid Profiling for Potential Applications - Rufai Fakai, Usman; Aliyu Saidu; Ibrahim Umar Muhammad; Adejumo MUTIU; Aminu Muhammad Bello; Abdulsalam Abdulrahman Ayodeji (Indonesian Scientific Publication, 2024)
This research investigates the physicochemical, phytochemical, and fatty acid composition of Neocaryamacrophylla seed oil, sourced from Illela, Sokoto State, Nigeria. Employing a soxhlet extraction method with n-hexane, the study determined a saponification value of 153.33 mgKOH/g, iodine value of 33.07 gI2/100g, and a peroxide value of 45.5 mgmeq/kg. Qualitative phytochemical analysis revealed the presence of tannins, saponins, flavonoids, alkaloids, steroids, and terpenoids, aligning with the antimicrobial attributes noted in Anacardiumoccidentale L. seeds oil. Fatty acid profiling identified oleic acid as the predominant monounsaturated fatty acid (42.46%), while linoleic and arachidonic acids constituted the main polyunsaturated fatty acids (35.08%). The study's findings suggest potential applications of Neocaryamacrophylla seed oil in soap production, owing to its high saponification value, and its stability, indicated by the MUFA/PUFA ratio. This research contributes valuable insights into the underexplored properties of Neocaryamacrophylla seed oil, holding implications for industries seeking alternative oil sources.